The Marketing Mix and Purchasing Decision Process on Laptop Computer in The Republic of the Union of Myanmar - นนทวุฒิสวัสดิ์ ศิวฤทธิ์; วิวัฒนชาต ศศนันท์; เสมอใจ ฉัตยาพร (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
This research aimed to study the marketing mix and purchasing decision process on Laptop computer in the Republic of the Union of Myanmar, to compare level of marketing mix and purchasing decision process on Laptop computer in the Republic of the Union of Myanmar classified by demographics, and to study the relationship between the marketing mix and purchasing decision process on Laptop computer in the Republic of the Union of Myanmar. A questionnaire was used to collect data from 385 consumers who purchased laptops in Republic of the Union of Myanmar. Data was analyzed by using frequency, percentage, Standard Deviation, t-test, One-way ANOVA, LSD and Pearson Product Moment Correlation Analysis. The results revealed that marketing mix of laptops in Republic of the Union of Myanmar in the overview was at a high level, whereas price and product were at the highest level, place, and promotion were at a high level respectively. Purchasing decision process for laptops in Republic of the Union of Myanmar in the overview was at a high level, whereas feeling after purchasing, decision making and alternatives evaluation were at the highest level, perception on demands or problems and information searching were at a high level respectively. Respondents with different genders, ages, occupations, educational levels, and incomes had different opinions on marketing mix and purchasing decision process on laptops in Republic of the Union of Myanmar with statistically significant at .05 level. Marketing mix and purchasing decision process had a positive correlation at a moderate level with statistically significant at .01 level.